Self-Concept Used by Autonomous Multilingual Learner for Improving Speaking Ability - Elbagiz, Anna Ashry Savirah; Adityo (Indonesian Values and Character Education Journal, 2023)
English for good communication among countries due to the related phenomenon, nowadays, there are increasingly diverse of society from their ways of spoken languages or expressing their life. There are several difficulties in learning foreign languages such as insecurity of dual abilities, comments from other people, unwillingness to learn, fear of taking a risk for correcting other people’s oversight, difficulty to get the facilities, and getting rid of boredom. The purpose of this research is to analyze the self-concept used by Fiki Naki as an autonomous multilingual learner. To be more detailed, the present research analyzes the self-concept or the ways of autonomous language learning that Fiki Naki uses by utilizing social technology such as Fiki Naki’s Youtube,  Podcast, and Maxstream for improving his speaking ability. This research used a document analysis as a qualitative research method and Fiki Naki’s YouTube videos will be the research object for completing the analysis. There is three steps model in data analyzing such as; data reduction, data presentation, and conclusion drawing /verification. The findings describe some ways that he used to master the basics of various languages. Later on, this research will be turned into a reference for language researchers to develop the concept of autonomous language learning.